Representation of Power Relation in Sundanese Myth in Kurniawan’s Man Tiger: A Strauss’ Structuralism AnalysisRepresentation of Power Relation in Sundanese Myth in Kurniawan’s Man Tiger: A Strauss’ Structuralism Analysis - Rifai, Ahmad Abu; Hetami, Fatma (Universitas Negeri Semarang, 2022)
Myth is an important part of the history of Indonesian civilization. This study tries to reveal the position of tigers as a myth believed in Sundanese society. In conducting the research, textual analysis by using Kurniawan’s Man Tiger as the primary data was employed. The researcher analyzed how the tiger as a symbol in Sundanese myth represents a specific power relation in society. Levi-Strauss’ structuralism was used. After determining units, episodes, and mythemes, binary opposition was used to reveal the meanings. The results of the study show that Man Tiger has eight episodes. It is also found out that there are different power relations established by two basic situations, namely Sundanese traditional and urban societies. In Sundanese traditional society, tiger owners are considered heroes because they protect people from both invaders and robbers. Because of this, they are put in a high place. These beliefs and power relations are very evident in the sphere of traditional society, while they begin to fade in the urban society. In other words, Sundanese traditional society has a myth-based-power relation showing that the tigers’ owner have notable and high position, while the urban society socially has no power relation based on myth.